2002
DOI: 10.1200/jco.20.2.485
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychologic Impact of Standard-Dose Systemic Chemotherapy in Long-Term Survivors of Breast Cancer and Lymphoma

Abstract: Data from this study support the hypothesis that systemic chemotherapy can have a negative impact on cognitive functioning as measured by standardized neuropsychologic tests and self-report of memory changes. However, analysis of the Neuropsychological Performance Index suggests that only a subgroup of survivors may experience long-term cognitive deficits associated with systemic chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
215
1
10

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 473 publications
(244 citation statements)
references
References 18 publications
18
215
1
10
Order By: Relevance
“…The lack of strong associations between performance on neuropsychological tests and self-reported neurocognitive function is not uncommon [30][31][32][33]. This apparent disparity has resulted in polarizing views among researchers and clinicians in the field about which is the most valid and clinically useful measure.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of strong associations between performance on neuropsychological tests and self-reported neurocognitive function is not uncommon [30][31][32][33]. This apparent disparity has resulted in polarizing views among researchers and clinicians in the field about which is the most valid and clinically useful measure.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to note that the researchers included both pre-and peri-menopausal women in their study, further limiting the conclusion that TAM, as opposed to menopause, had affected cognition. Lack of control for menopausal status is also characteristic of other studies [3,4].…”
Section: Introductionmentioning
confidence: 94%
“…Since chemotherapy itself may have detrimental cognitive effects in breast cancer patients [22][23][24], and significant differences were not obtained on these measures when TAM and chemotherapy users were compared to survivors who had only received chemotherapy, it is difficult to conclude that any cognitive difficulties could be solely attributed to TAM. Another study comparing high-and standard-dose chemotherapy treatments found no cognitive differences between TAM and no TAM subgroups of patients on any measure in a comprehensive test battery [3], but only 4 of the women tested were current users of TAM, rendering this finding similarly inconclusive.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations